KRITIK AKAL DAN HISTORIS DALAM PEMIKIRAN MOHAMMED ARKOUN: TONGGAK FILSAFAT ISLAM MODERN - Fithri Choirunnisa Siregar; Riki Saputra; Rusydi (STKIP Subang, 2026)
This study aims to explore Mohammed Arkoun's thought on the critique of reason and the dimension of historicity as the foundation of modern Islamic philosophy. Arkoun perceives that contemporary Islamic thought is trapped in a